Evaluasi Penggunaan Obat Antiemetik pada Penderita Kanker Payudara Pasca Kemoterapi: Evaluation of Antiemetic Drugs Use in Breast Cancer Patients After Chemotherapy - Dhea Amanda Sabilla Fauzi; Hajrah Hajrah; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Data from the Ministry of Health Republic Indonesia in 2018 showed 42,100 women had breast cancer. Chemotherapy is the main choice of treatment for treating cancer, but it has several side effects, such as nausea and vomiting. The aims of this research, to identify characteristics breast cancer patient, classification risk of chemotherapy induce of nausea and vomiting also appropriate use of antiemetic to prevent chemotherapy side effect. Observational research had been use for this study with retrospective data collection based on patient medical records in January-December 2020. The results showed that breast cancer patients were women with age range of 46-55 years with percentage 38.1% and 33.33% had Body Mass Index (BMI) Obesity I. Combination of Antibiotics and Taxanes is the most widely used by 71.45% and has the most common risk classification of moderate nausea and vomiting. The most widely used antiemetic is a combination of 5-Hydroxitryptamine-3, Antagonists Histamine 2, and Dexamethasone. 96.2% compliance with antiemetic use was achieved and 3.8% was not achieved.